Putting the spotlight on small cloud droplets with SmHOLIMO – a new holographic imager for in situ measurements of clouds - C. Fuchs; F. Ramelli; D. Schweizer; U. Lohmann; J. Henneberger (Atmospheric Measurement Techniques, 2025)
The microstructure of liquid and mixed-phase clouds is characterized by the cloud droplet size distribution (CDSD), which influences the cloud evolution and its interaction with radiation. However, state-of-the-art cloud probes still face challenges because they require either platforms that move at constant speed or inlets that can directly alter the actual CDSD. Therefore, precise and accurate in situ measurements of CDSDs, especially of cloud droplets smaller than 6 µm, are still lacking. This can lead to uncertainties in the microphysics and thus in weather and climate models, which are based on parameterizations often derived from these measurements.